PERTANGGUNGJAWABAN PIDANA DIREKSI PERUSAHAAN MASKAPAI PENERBANGAN SIPIL AKIBAT KECELAKAAN PESAWAT YANG MENIMBULKAN KORBAN JIWA BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 2009 TENTANG PENERBANGAN - Napitupulu, Titir Feronika; Effendi, Erdianto; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Some acts of directors have even led to criminal acts. For example, such as not doing aircraft maintenance, not doing a briefing (training) to the crew on duty, providing the wrong information even to corruption that causes a fatal problem in the flight system. There has been very little crime committed against directors when such crime is clearly possible because the board of directors is one of the legal subjects. The absence of punishment of directors is the background of this research.In accordance with the above description, the authors are interested to conduct research under the title Criminal Accountability Board of Directors of Civil Airlines Companies Due to Accident Aircraft That Increase Mental Victims Based on Law Number 1 Year 2009 About Aviation. This thesis aims to find out whether the directors of airline companies can be sentenced to death if the plane crashes that cause casualties and to know the cause of menagapa so far no directors are punished while the law regulates criminal sanctions if someone has made a mistake in flight.This type of research can be classified in the type of normative legal research, which is to examine the legal norms derived from the rule of law that is the law. This research is done by examining the literature or secondary material that formulated normative research or library research books. In terms of nature of this research is a description that is the purpose of describing or describe clearly and detailed.From the research results of the problem there are two things that can be concluded, first, the punishment of the board of directors can be done in accordance with the Law of Limited Liability Company and Aviation Act. Secondly, airline directors are rarely punished because flight technology is so high that it is difficult to conduct an investigation, it is difficult to determine which includes the actions of directors and employees and various other reasons.Keywords: Accountability, Flight Directors